Metodologia para maximização da inserção da geração fotovoltaica nas redes de distribuição de baixa tensão - Darui, Caroline Beatriz Fucks (2020)
Not long ago, the electricity system was organized into a generation system, away from consumption centers and a transmission system that carried energy for long periods until it reached the distribution system, where consumers are connected. In this format, the energy flow was always unidirectional, from the generation system to the loads. With the emergence of distributed generation (DG), mainly by photovoltaic energy (PV), the Brazilian distribution system goes through a transformation process, in which it starts to aggregate these generation sources, distributed along its extension, injecting energy into the network, which provides bidirectional energy flow. The GD of a renewable source has several benefits, mainly with regard to the contribution to meet the demand for energy; however, excessive penetration can cause reverse energy flow and negative impacts on the power quality of the network. Utilities are afraid of suffering the consequences of reduced revenues (due to the drop in energy sales), coupled with the need for network maintenance and new investments. In order to prevent operational limits from being violated and that utilities lose their reliability, it is important to know the capacity that each system has to host new network agents (PV). In this sense, this work proposes a methodology to maximize the insertion of photovoltaic generation in low voltage distribution networks, by determining the potential for insertion of photovoltaic generation (PI) of the network, technical parameters for the PV to benefit all agents of the distribution system. The methodology is implemented through an interface between MATLAB® and OpenDSS® software. The installed energy of the generation system for each consumer is considered to be proportional to its maximum demand. This percentage is the same for all consumers. Through the exhaustive search process, the best condition is found, which should indicate the greater generation capacity of consumers without affecting the voltage levels, power factor (pf) and network load. The proposed model proved to be more optimistic in the network's capacity to host PV systems in relation to methods that consider random PV insertion.